Differential methylation of lncRNA KCNQ1OT1 promoter polymorphism was associated with symptomatic cardiac long QT. (August 2017) - Coto, Eliecer; Calvo, David; Reguero, Julián R; Morís, César; Rubín, Jose M; Díaz-Corte, Carmen; Gil-Peña, Helena; Alosno, Belén; Iglesias, Sara; Gómez, Juan
Aim: To investigate whether the differential methylation of KCNQ1OT1 was associated with the risk of symptomatic long QTc.Patients & methods: We investigated the methylation status of KCNQ1OT1 in a cohort of patients (n = 131) with a symptomatic prolonged QTc. All the patients were genotyped for a common promoter polymorphism (rs11023840). They were also genotyped for DNA digested with the methylation-sensitive HpaII restriction enzyme.Results: We found a significant higher frequency of AA genotype (p = 0.02) in the patients compared with healthy controls (n = 240). In the HpaII -digested samples there was a higher frequency of the A-allele among the patients compared with the controls (p = 0.02).Conclusion: Our findings supported a role for the differential methylation/imprinting of KCNQ1OT1 in the risk for symptomatic prolonged QTc.